2023
DOI: 10.1371/journal.pone.0283394
|View full text |Cite|
|
Sign up to set email alerts
|

Testosterone treatment combined with exercise to improve muscle strength, physical function and quality of life in men affected by inclusion body myositis: A randomised, double-blind, placebo-controlled, crossover trial

Abstract: Introduction Inclusion body myositis (IBM) is the most commonly acquired skeletal muscle disease of older adults involving both autoimmune attack and muscle degeneration. As exercise training can improve outcomes in IBM, this study assessed whether a combination of testosterone supplementation and exercise training would improve muscle strength, physical function and quality of life in men affected by IBM, more than exercise alone. Methods This pilot study was a single site randomised, double-blind, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, while this review and meta-analysis did not include studies combining conservative non-pharmacological treatments with pharmacological interventions, preventing a direct comparison of their effectiveness, previous research in MD and NMD suggests that conservative non-pharmacological interventions have comparable, if not superior, effectiveness than pharmacological treatments. 60 61 For instance, very large, although non-significant, ESs (range: 1.46–8.93) strongly favoured conservative interventions over pharmacological treatments in specific outcomes (e.g. Berg balance, grip strength, 2-min walk test, physical functioning, role limitations due to physical health and emotional problems) in the study by Connor et al .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, while this review and meta-analysis did not include studies combining conservative non-pharmacological treatments with pharmacological interventions, preventing a direct comparison of their effectiveness, previous research in MD and NMD suggests that conservative non-pharmacological interventions have comparable, if not superior, effectiveness than pharmacological treatments. 60 61 For instance, very large, although non-significant, ESs (range: 1.46–8.93) strongly favoured conservative interventions over pharmacological treatments in specific outcomes (e.g. Berg balance, grip strength, 2-min walk test, physical functioning, role limitations due to physical health and emotional problems) in the study by Connor et al .…”
Section: Discussionmentioning
confidence: 93%
“…60 61 For instance, very large, although non-significant, ESs (range: 1.46-8.93) strongly favoured conservative interventions over pharmacological treatments in specific outcomes (e.g. Berg balance, grip strength, 2-min walk test, physical functioning, role limitations due to physical health and emotional problems) in the study by Connor et al 60 Numerous questions regarding the effectiveness of these interventions remain unanswered, specifically about certain outcomes, populations and intervention types. Pain, a common and distressing symptom in MD, 62 63 offers anecdotal indications of potential relief through non-pharmacological interventions such as hydrotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides pharmacological agents, different exercise regimens have been assessed as possible therapeutic approaches for sIBM [ 248 , 249 , 250 , 251 , 252 , 253 ]. These studies eliminated the concern of exercise being potentially harmful and demonstrated that physical activity ameliorates strength in sIBM patients.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Non-pharmacological treatment includes physical therapy of the affected muscles to prevent disuse atrophy. A single site randomised, double-blind, placebo-controlled, crossover study assessed whether a combination of testosterone supplementation and exercise training would improve muscle strength, physical function and quality of life in men affected by IBM, more than exercise alone (103). Exercise and transdermal testosterone and placebo (exercise and placebo cream) were each delivered for 12 weeks, with a two-week wash-out between the two periods.…”
Section: Take-home Messagesmentioning
confidence: 99%